Greenpeace Campaigns Against Asia Pulp & Paper and Wilmar International: A Comparative Research - Sitorus, Syifa Adzraa; Purnama, Chandra (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
As an International Non-Governmental Organization (INGO), for years, Greenpeace has waged campaigns against rainforest deforestation in Indonesia by multinational corporations, such as Asia Pulp & Paper and Wilmar International, the top players in their respective industries. This study reviews the similarities and differences in campaign strategies used by Greenpeace against APP and Wilmar while showing the process of global media communication. The research was conducted as a comparative study using qualitative methods based on the Sandman Environmental Communication Model. Data collected from documents and audio-visual materials passed through a triangulation process to cross-check its interpretation. Eventually, this research finds that Greenpeace relied on the image of well-loved characters like Barbie to create intrigue in its